2000
DOI: 10.1063/1.373843
|View full text |Cite
|
Sign up to set email alerts
|

A delay of percolation time in carbon-black-filled conductive polymer composites

Abstract: This work attempts to determine how percolation at an equilibrium state is correlated to percolation under experimental conditions. The dynamic process of forming conductive networks in carbon-black (CB)-filled poly(methyl methacrylate) composites was investigated by real-time tracing the time dependence of electrical resistivity during isothermal treatments. It was observed that the dynamic percolation curves maintains the same shape and shift to a shorter percolation time with increasing annealing temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
102
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 17 publications
5
102
1
Order By: Relevance
“…In both directions t BD reduces with higher V A which is consistent with a dynamic percolation scenario [9,13,29]. This voltage dependent resistance breakdown is similar to the electric field driven dynamic percolation of conducting particles suspended in nonconducting polymers [30,31]. Fig.…”
supporting
confidence: 70%
“…In both directions t BD reduces with higher V A which is consistent with a dynamic percolation scenario [9,13,29]. This voltage dependent resistance breakdown is similar to the electric field driven dynamic percolation of conducting particles suspended in nonconducting polymers [30,31]. Fig.…”
supporting
confidence: 70%
“…The several orders of magnitude variation in the values of percolation thresholds reported in the literature can often be attributed to the phenomenon of dynamic percolation. Dynamic percolation has been observed in both CNT- [27][28][29][30][31][32] and carbon black-loaded [33][34][35] polymer composites and describes the dynamic process of conductive network formation.…”
Section: Introductionmentioning
confidence: 99%
“…It means that, for the same concentration of nanofiller, a polymer composite can show very different conductivity levels as a result of different processing/thermal histories. Such phenomenon has been observed for one-dimensional (1D) carbon nanofillers like carbon nanotubes (CNT) 24,27,[30][31][32] and zero-dimensional (0D) carbon black 28,33 filled polymer composites. Deng et al 34 reported a near five-time reduction in percolation threshold for oriented CNT/polypropylene (PP) tapes after annealing, while Zhang et al 27 found that the electrical conductivity of annealed films based on CNT/thermoplastic polyurethane (TPU) was up to eight orders of magnitude higher than that of as-extruded compound.…”
Section: Research Articlementioning
confidence: 99%